Evaluasi Yuridis Kewenangan Delegasi dan Mandat dalam Penyelenggaraan Administrasi Negara: Suatu Kajian Normatif - Abdul Jabar; Evi Yuniarni; Dwi Fefri Kurniasari (WELFARE STATE Jurnal Hukum, 2026)
Delegation of authority through delegation and mandate mechanisms constitutes a strategic instrument in public administration to support the effectiveness and efficiency of public service delivery. This study aims to analyze the practice of authority delegation within government institutions and examine its juridical implications for accountability and the quality of public services. The research employs a normative juridical approach by reviewing statutory regulations and their practical implementation. The findings indicate that although the regulation of delegation and mandate has been normatively established in Law Number 30 of 2014 concerning Government Administration, its implementation still faces various challenges. The primary issues lie in the unclear distinction between delegation and mandate, as well as the ambiguity of legal accountability. Furthermore, the use of mandates without substantive transfer of responsibility leads to delays in public service processes. Weak supervisory mechanisms over the delegation of authority also contribute to decreased efficiency and responsiveness. Therefore, there is a need for clearer technical regulations and the strengthening of government officials’ capacity to ensure that the delegation of authority is carried out in an accountable, effective manner and in accordance with the general principles of good governance.